Combined process of electrocoagulation and photocatalytic degradation for the treatment of olive washing wastewater - Ates, Hasan; Dizge, Nadir; Yatmaz, Hüseyin Cengiz (Iwa Publishing, 2017)
In this study, an electrocoagulation reactor (ECR) and photocatalytic reactor (PCR) were tested to understand the performance of combined electrocoagulation and photocatalytic-degradation of olive washing wastewater (OWW). The effects of initial pH (6.0, 6.9, 8.0, 9.0), applied voltage (10.0, 12.5, 15.0 V), and operating time (30, 60, 90, 120 min) were investigated in the electrocoagulation reactor when aluminum electrodes were used as both anode and cathode. The pH, conductivity, color, chemical oxygen demand (COD), and phenol were measured versus time to determine the efficiency of the ECR and PCR process. It was observed that electrocoagulation as a single treatment process supplied the COD removal of 62.5%, color removal of 98.1%, and total phenol removal of 87% at optimum conditions as pH 6.9, applied voltage of 12.5 V, and operating time of 120 min. Moreover, final pH and conductivity were 7.7 and 980 mu S/cm, respectively. On the other hand, the effect of semiconductor catalyst type (TiO2 and ZnO) and loading (1, 2, 3 g/L) were tested using PCR as a stand-alone technique. It was found that photocatalytic degradation as a single treatment process when using 1 g/L ZnO achieved the COD removal of 46%, color removal of 99% with a total phenol removal of 41% at optimum conditions. Final pH and conductivity were 6.2 and 915 mu S/cm, respectively. Among semiconductor catalysts, TiO2 and ZnO performed identical efficiencies for both COD and total phenol removal. Moreover, combination in which electrochemical degradation was employed as a pre-treatment to the photocatalytic degradation process obtained high COD removal of 88% and total phenol, as well as color removal of 100% for the OWW. The electrochemical treatment alone was not effective, but in combination with the photocatalytic process, led to a high-quality effluent. Finally, sludge collected from the electrocoagulation process was characterized by attenuated total reflection Fourier transform infrared and X-ray powder diffraction analyses.
Keywords: combined process; electrocoagulation; olive washing wastewater; photocatalysis